Mid-century change analysis of temperature and precipitation maxima in the Swat River Basin, Pakistan - Ali, Waqar; Hashmi, Muhammad Zia; Jamil, Asma; Rasheed, Sajida; Akbar, Saima; Iqbal, Hamid (Frontiers in Environmental Science, 2022)
The study analyses trends in historical (1989-2018) and projected (2041-2060) temperature and precipitation maxima in the Swat River Basin, Pakistan. This basin has a history of climate related disasters which are becoming more intense and more frequent due to changing climate which has direct impacts on life and livelihood safety of the local communities. Major livelihood sources are agriculture and tourism, both highly sensitive to extreme climate events. Therefore, it becomes very important to assess the future trends of local temperature and precipitation extreme events. For observed data, non-parametric tests were employed, while for projection, Statistical Downscaling Model (SDSM) with CanESM2 GCM under three scenarios (RCP 2.6, 4.5 and 8.5) was used. The R2 value between monthly observed and simulated temperature varied between 0.82 to 0.91 and 0.92 to 0.96 for training and confirmation periods, respectively. For areal precipitation, R2 value of 0.49 was noted for calibration and 0.35 for validation. Observed temperature showed insignificant decreasing trend at all stations except Saidu Sharif, while precipitation showed increasing trend at two (Kalam and Malam Jabba) stations and decreasing trend at other two (Dir and Saidu Sharif). More than 2 ºC rise was noticed in annual maximum projected (2041 to 2060) temperature (Areal and Dir), while for Kalam, Malam Jabba and Saidu Sharif, around 1 ºC rise was observed. Likewise, almost 12% increase is occurred in annual maximum (areal) and seasonal precipitation (summer and autumn) under all scenarios except RCP 4.5 for which 20% and 32% increase was noted in summer and autumn seasons, respectively. The performance of SDSM in simulating maximum temperature and precipitation was satisfactory.